Sorption, Release and Forms of Mercury in Contaminated Soils Stabilized with Water Treatment Residual Nanoparticles. (20th June 2016) - Elkhatib, Elsayed; Moharem, Mohamed; Mahdy, Ahmed; Mesalem, Mohamed
Abstract: This study was carried out to assess, for the first time, the effect of water treatment residual nanoparticles (nWTR) on mobility, fractionation and speciation of Hg in two arid zone soils. Nanoscale water treatment residual application markedly reduced cumulative Hg released from soils studied, with the effect increasing as the nWTR application rate increases. The power function kinetic model well described the desorption process from soils and soils with nWTR. Meanwhile, application of nWTR greatly increased the association of Hg with the residual fraction and increased the most stable Hg species (Hg (OH)2 amor), which in turn enhanced Hg immobilization in the studied soils. Fourier transmission infrared spectroscopy analysis indicated the involvement of nWTR in the retention of Hg (II) and revealed that sorption occurred mainly through OH groups, which suggest inner‐sphere adsorption of Hg ions to surface functional groups on nWTR. These results demonstrated the feasibility of using a green and low‐cost nWTR as best management practice to retain and immobilize excess Hg in contaminated soils. Copyright © 2016 John Wiley & Sons, Ltd.